Anti-hypertensive drugs have different effects on ventricular hypertrophy regression - Ferreira Filho, Celso; Abreu, Luiz Carlos de; Valenti, Vitor E.; Ferreira, Marcelo; Meneghini, Adriano; Silveira, José Alexandre; Riera, Andrés R. Pérez; Colombari, Eduardo [UNESP]; Murad, Neif; Santos-Silva, Paulo Roberto; Silva, Lovian José Henrique Pereira da; Vanderlei, Luiz Carlos Marques [UNESP]; et al. (Universidade de São Paulo (USP), Faculdade de Medicina, 2010)
OBJECTIVES: There is a direct relationship between the regression of left ventricular hypertrophy (LVH) and a decreased risk of mortality. This investigation aimed to describe the effects of anti-hypertensive drugs on cardiac hypertrophy through a meta-analysis of the literature. METHODS: The Medline (via PubMed), Lilacs and Scielo databases were searched using the subject keywords cardiac hypertrophy, antihypertensive and mortality. We aimed to analyze the effect of anti-hypertensive drugs on ventricle hypertrophy. RESULTS: The main drugs we described were enalapril, verapamil, nifedipine, indapamina, losartan, angiotensin-converting enzyme inhibitors and atenolol. These drugs are usually used in follow up programs, however, the studies we investigated used different protocols. Enalapril (angiotensin-converting enzyme inhibitor) and verapamil (Ca++ channel blocker) caused hypertrophy to regress in LVH rats. The effects of enalapril and nifedipine (Ca++ channel blocker) were similar. Indapamina (diuretic) had a stronger effect than enalapril, and losartan (angiotensin II receptor type 1 (AT1) receptor antagonist) produced better results than atenolol (selective β1 receptor antagonist) with respect to LVH regression. CONCLUSION: The anti-hypertensive drugs induced various degrees of hypertrophic regression.
Keywords: Hypertrophy; Cardiomyopathy; Hypertrophic; Left ventricle hypertension; Cardiology